Effect of Local Anaesthesia with and without Adrenaline on Blood Pressure, Pulse Rate and Oxygen Saturation - A Comparative Study - Yadav, Deepak; Bali, Harleen; Mishra, Ravish; Kandel, Laxmi; Khanduri, Nitin; Tripathi, Shashank; Singh, Sunil Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Most of the minor oral surgical procedures are performed under local anaesthesia (LA). Vasoconstrictor present in LA decreases the rapid absorption of LA, decreases systemic toxicity, increases duration of LA and provides local hemostasis which favor clinicians for better work performance. But it is also known to increase heart rate (HR) and blood pressure (BP). Objective: To evaluate the effect of vasoconstrictor adrenaline 1:80,000 in 1.8 ml of 2% Lidocaine on systolic and diastolic blood pressure, pulse rate and oxygen saturation of normotensive patients. Methods: A prospective randomized study was conducted on 70 patients who were divided randomly into 2 parallel groups according to the LA received. Group 1 (G1): lidocaine 2% without adrenaline and Group 2 (G2): lidocaine 2% with adrenaline 1:80,000. Blood pressure, pulse rate and oxygen saturation were measured before and 10 minutes after LA administration for each patient. Results: Statistically significant rise in blood pressure and pulse rate was seen in group receiving LA with adrenaline (G2) 10 minutes after administration. Conclusion: Though adrenaline amount in 1.8ml causes significant rise of parameters assessed under the study, the rise is not clinically relevant for a normotensive, medically fit patient.